2020
DOI: 10.1073/pnas.1922272117
|View full text |Cite
|
Sign up to set email alerts
|

Clonemate cotransmission supports a role for kin selection in a puppeteer parasite

Abstract: Host manipulation by parasites is a fascinating evolutionary outcome, but adaptive scenarios that often accompany even iconic examples in this popular field of study are speculative. Kin selection has been invoked as a means of explaining the evolution of an altruistic-based, host-manipulating behavior caused by larvae of the lancet flukeDicrocoelium dendriticumin ants. Specifically, cotransmission of larval clonemates from a snail first host to an ant second host is presumed to lead to a puppeteer parasite in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 58 publications
2
20
1
Order By: Relevance
“…We identified genetically identical parasites (clones) in 12 of 14 definitive hosts studied, a finding consistent with previous studies in livestock, where 61% and 85% of hosts studied contained genetically identical parasites ( Vilas et al, 2012 , Beesley et al, 2017 ). This supports the theory that following clonal expansion within the snail, there is some co-transmission of clonemates to the definitive host, similar to previous reports ( Beesley et al, 2017 ), but does not extend to the low clonal diversity observed in sheep for F. hepatica ( Vilas et al, 2012 ), and it does not occur to the same extent as clonemate co-transmission recently observed for D. dendriticum ( Criscione et al, 2020 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We identified genetically identical parasites (clones) in 12 of 14 definitive hosts studied, a finding consistent with previous studies in livestock, where 61% and 85% of hosts studied contained genetically identical parasites ( Vilas et al, 2012 , Beesley et al, 2017 ). This supports the theory that following clonal expansion within the snail, there is some co-transmission of clonemates to the definitive host, similar to previous reports ( Beesley et al, 2017 ), but does not extend to the low clonal diversity observed in sheep for F. hepatica ( Vilas et al, 2012 ), and it does not occur to the same extent as clonemate co-transmission recently observed for D. dendriticum ( Criscione et al, 2020 ).…”
Section: Discussionsupporting
confidence: 91%
“…A recent study in the trematode Dicrocoelium dendriticum (land snail-ant-ungulate) revealed the lowest clonal diversity for any trematode to date, with only 54 of 272 (19.9%) genotypes being unique. This observation was consistent with the restricted movements of the snails and ants under investigation, and the likely localised adherence of the slime balls, containing the cercariae, that infect the ant ( Criscione et al, 2020 ). Appreciating the geographical scale over which studies are conducted facilitates their interpretation.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…Parasites face a central problem: how to maximize transmission to the next host. This has driven the evolution of a wide variety of lifecycle features to facilitate parasite transmission [ 1 , 2 ]. However, perhaps the most common transmission strategy is to produce vast numbers of infective stages [ 3 , p. 20].…”
Section: Introductionmentioning
confidence: 99%
“…Parasites face a central problem: how to maximize transmission to the next host. This has driven the evolution of a wide variety of lifecycle features to facilitate parasite transmission (Criscione et al, 2020;Vasudevan et al, 2015). However, perhaps the most common transmission strategy is to produce vast numbers of infective stages (Loker and Hofkin, 2015, p. 20).…”
Section: Introductionmentioning
confidence: 99%